Assessment of the risk of road embankment instability due to water filtration using fully coupled numerical analysis - Miłosz Just (Archives of Civil Engineering)
The cut-off walls of infrastructural ground structures are a vital aspect of geotechnical engineering, with the array of available technologies in this domain continually expanding. Polyvinyl chloride (PVC) sheet pile walls are gaining popularity and have become a significant choice in design solutions, despite the long-standing recognition of sheet pile walls in their traditional steel form. This paper presents a case study focusing on a road embankment of a Provincial Road number 181 in Poland. It provides a historical perspective of the embankment, details the soil and water conditions of the area, and conducts an extensive analysis of filtration through embankment at various construction stages using the Finite Element Method. The study offers insights into the three-dimensional model, incorporating a fully coupled stress and seepage analysis. The results encompass water flow paths, slope stability, and displacements before and after the construction of the impermeable barrier, providing a comprehensive view of this modern and eco-friendly engineering solution.